経静脈的コイル塞栓術を施行後に全摘出した下顎骨動静脈奇形の1例 - 高戸, 毅; 庄島, 正明; 阿部, 雅修; 安部, 貴大; 星, 和人; 西條, 英人 (日本口腔外科学会雑誌, 2015)
Arteriovenous malformation rarely occurs in mandibular bones. We describe our experience with a case of arteriovenous malformation arising in the mandible that could be completely extirpated surgically after transvenous coil embolization. A 10-year-old girl had left mandibular swelling, and slight but frequent bleeding from the left lower gingiva. The molars in the left mandible were unstable. Panorama X ray films, computed tomography, and magnetic resonance imaging showed the presence of an arteriovenous malformation approximately 5 cm in diameter, arising between the premolars and molars of the left mandible. After transvenous embolization with the use of a platinum coil (total 1800 cm), the mass of abnormal vessels and the lower premolars and molars with some adjacent tissue were surgically resected. Because the inferior border and lingual cortex of the left side of the mandible were sufficiently preserved, neither subsequent fixation with plates and screws nor reconstruction with a tissue graft was needed. The blood loss was 720 mL, and blood transfusion was not necessary. One year after surgery, there was no evidence of recurrence of arteriovenous malformation, and additional bone had newly formed from the resection margin of the mandibular bone.